Physiological comparison of intensity-controlled, isocaloric intermittent and continuous exercise†. Issue 10 (26th November 2018) - Combes, Adrien; Dekerle, Jeanne; Bougault, Valérie; Daussin, Frédéric N.
Abstract: VO2 fluctuations are argued to be an important mechanism underpinning chronic adaptations following interval training. We compared the effect of exercise modality, continuous vs. intermittent realized at a same intensity, on electrical muscular activity, muscular oxygenation and on whole body oxygen uptake. Twelve participants (24 ± 5 years; VO2peak: 43 ± 6 mL· min −1 ·kg −1 ) performed (i) an incremental test to exhaustion to determine peak work rate (WRpeak ); two randomized isocaloric exercises at 70%WRpeak; (ii) 1 bout of 30 min; (iii) 30 bouts of 1 min work intercepted with 1 min passive recovery. For electromyography, only the CON exercise showed change for the vastus lateralis root-mean-square (+6.4 ± 5.1%, P < .01, 95%CI 3.2, 8.3) and mean power frequency (−5.2 ± 4.8, P < .01, 95%CI −8.2, −3.5). Metabolic fluctuations (i.e. Oxygen Fluctuation Index and HHb Fluctuation Index) were higher in the intermittent modality, while post-exercise blood lactate concentrations (4.80 ± 1.50 vs . 2.32 ± 1.21 mM, respectively, for the CON and INT, P < .01, 95%CI 1.72, 3.12) and the time spent over 90% of VO2 target (1644 ± 152 vs . 356 ± 301 sec, respectively, for the CON and INT, P < .01, 95%CI 1130, 1446) were higher in the continuous modality. In conclusion, despite a similar energy expenditure and intensity, intermittent and continuous exercises showed two very different physiological responses. The intermittent modality would lead to a larger recruitment of fast twitch fibres that are less mitochondria-equipped and therefore may be more likely respondent to mitochondrial adaptations. In addition, this modality induces greater metabolic variations, a stimulus who could lead to mitochondrial development.